Pemanfaatan WAKEPO dalam Mendorong Civic Participation pada Pembuatan Surat Keterangan Online di Desa Ganeas : Penelitian - Siti Patimah; Prayoga Bestari; Nisrina Nurul Insani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to describe the utilization of the WhatsApp Kebutuhan Informasi dan Pelayanan Online (WAKEPO) in the process of issuing official letters in Ganeas Village, Ganeas Subdistrict, Sumedang Regency, as well as to analyze its contribution to enhancing civic participation among rural communities. A qualitative approach was employed using a case study method. Data were collected through in-depth interviews, field observations, and documentation. The findings show that WAKEPO simplifies the flow of village administrative services through its integration with the e-Office system, enabling citizens to request letters remotely, quickly, and free of charge. This service greatly benefits residents who live far from the village office or who are currently living outside the village, and it reduces the dependency on the physical presence of the village head for document signing. Moreover, the active involvement of the community in independently using the service reflects strong participation in digital public services. WAKEPO functions not only as a technical instrument but also strengthens the social bond between the community and the village government. These findings affirm that the digitalization of public services in rural areas can serve as an effective strategy for building more inclusive, responsive, and participatory local governance.